2019
DOI: 10.1590/0034-7167-2017-0685
|View full text |Cite
|
Sign up to set email alerts
|

Management of prenatal nursing care at a Health Center in Angola

Abstract: Objective: To understand how care management in prenatal care in a Care Center in Angola happens. Method: A qualitative study, which used the Constructivist Grounded Theory (GT) as a methodological framework. The theoretical sample consisted of 22 participants, including nursing professionals, pregnant women and nursing students from Huambo, Angola. The data were collected by interviews and analyzed according to initial and focused coding. Results: Five categories arose: Embracing the pregnant woman for pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
3
0
6
Order By: Relevance
“…Similarly, the study proceeded to the content analysis of each code of the Nursing Care Administration thematic group. It verified the micropolitical action of nurses (21)(22) , through the definition code, in the excerpts "the managerial attribution falls on the nurse in the health services", "they aim to aid other people (23) ", "For the quality of care as a citizen's right (15,17,(21)(22)(24)(25)(26)(27)(28)(29)(30)(31) ", as well as the adoption of locoregional and network strategies, as seen in the example taken from the code Ways:…”
Section: Expert Opinion Devoid Of Critical Evaluation or Based On Bas...mentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, the study proceeded to the content analysis of each code of the Nursing Care Administration thematic group. It verified the micropolitical action of nurses (21)(22) , through the definition code, in the excerpts "the managerial attribution falls on the nurse in the health services", "they aim to aid other people (23) ", "For the quality of care as a citizen's right (15,17,(21)(22)(24)(25)(26)(27)(28)(29)(30)(31) ", as well as the adoption of locoregional and network strategies, as seen in the example taken from the code Ways:…”
Section: Expert Opinion Devoid Of Critical Evaluation or Based On Bas...mentioning
confidence: 80%
“…The research observed that Care Management is focused on the proper functioning of the HCN -through the Ways Code, relating to the excerpts Health care networks/articulation in network (13)(14)(15)(16) ; Build a network of integral, humanized health services [...]; they bring a systemic conception, when considering the user's itinerary in the network and the interprofessional action for care management (9,12,16) .…”
Section: Expert Opinion Devoid Of Critical Evaluation or Based On Bas...mentioning
confidence: 99%
“…Estudo qualitativo realizado na Angola concluiu que a GC de enfermagem se efetiva nas relações de trabalho colaborativas centradas em palestras e consultas pré--natais, visando a construção de vínculo e relação dialógica com as gestantes e seus familiares. (23) Estudo brasileiro destaca que as usuárias, que recebem assistência do modelo de GC, relatam preferência pela consulta do enfermeiro no pré-natal e ressaltam o sentimento de segurança, ligado ao vínculo, ao afeto e ao cuidado pelos enfermeiros, acompanhado pela promoção do empoderamento e da autonomia do casal grávido. E os enfermeiros relatam que tiveram satisfação profissional quanto ao perceberem o impacto positivo prestado na vida das usuárias.…”
Section: Discussionunclassified
“…En contraste, (Errico et al 2018), indica que, en la atención prenatal de alto riesgo, los enfermeros pueden utilizar la consulta de enfermería considerando su dominio de las tecnologías livianas para involucrarse con tecnologías duras y livianas. Por otro lado, (Simão et al 2019), comentan que la gestión del cuidado de enfermería en el escenario de estudio es eficaz a través de pasos complementarios e interdependientes, basados en relaciones colaborativas entre profesionales y en el esfuerzo por establecer vínculos con las gestantes y sus familias.…”
Section: Análisisunclassified